Exploring the Influence of an E-Learning Sensory Processing-Based Module for Graduate Level Occupational Therapy Students on Clinical Reasoning: A Pilot Study. - Gee, Bryan M.; Strickland, Jane; Thompson, Kelly; Miller, Lucy Jane (Occupational Therapy International, 2017)
The purpose of this study was to explore the effectiveness of a series of online, module-based instructional reusable learning objects (RLOs) targeted at entry-level, 1st year, Master of Occupational Therapy students. The content of the RLOs addressed knowledge and implementation of A SECRET, a parental reasoning approach for children with a sensory processing disorder, specifically sensory over responsiveness. Nine RLOs were developed and embedded within a commonly used learningmanagement system. Participants (n = 8) were evaluated regarding their ability to discriminate between appropriate and inappropriate A SECRET strategies using a selected-response assessment. The participants' overall average score was 68%, a positive finding given the novelty of the instruction, assessment, and the content.